2021
DOI: 10.1177/03400352211023834
|View full text |Cite
|
Sign up to set email alerts
|

Saudi scholars’ perceptions and use of open government data portals at Shaqra University, Saudi Arabia

Abstract: This article reports the findings of a study on open data usage among Saudi scholars. It investigates the sample’s perceptions of open data and open data portals. The study reported the factors affecting the participants’ decision to use open data and aimed to understand Saudi researchers’ practices and perceptions related to the use and sharing of open data. It adopted a quantitative approach and a questionnaire was distributed to and collected from 190 Saudi academic staff to measure their perceptions, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Although the objectives, methodology and results differ from one study to another, all research analysed highlights the need to carry out studies on Saudi Arabia's OGD initiative, in order to highlight the barriers to its implementation, which is still in its early stages. Such a study will also help to clarify development directions, as well as encourage governments to pay more attention (Saxena, 2017(Saxena, , 2018(Saxena, , 2019Shehata & Elgllab, 2021). This study aims to achieve this objective.…”
Section: Open Government Data In Saudi Arabia: the Current Situationmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the objectives, methodology and results differ from one study to another, all research analysed highlights the need to carry out studies on Saudi Arabia's OGD initiative, in order to highlight the barriers to its implementation, which is still in its early stages. Such a study will also help to clarify development directions, as well as encourage governments to pay more attention (Saxena, 2017(Saxena, , 2018(Saxena, , 2019Shehata & Elgllab, 2021). This study aims to achieve this objective.…”
Section: Open Government Data In Saudi Arabia: the Current Situationmentioning
confidence: 97%
“…A recent study by Shehata and Elgllab (2021), which investigated Saudi scholars' perceptions of the Saudi OGD, found that the main issue is data quality, followed by the time needed to request and obtain data. The next most significant aspect, according to this study, was institutional barriers.…”
Section: Open Government Data In Saudi Arabia: the Current Situationmentioning
confidence: 99%
“…Perhaps the most prominent obstacle facing researchers is their inability to access data, in addition to the number of restrictions imposed on the use of data. Open data is data that can be accessed, reused or disseminated for any purpose, including for commercial use, without any publishing costs or restrictions (Shehata and Elgllab, 2021). The main driver for Arab governments to establish open data portals is their desire to achieve transparency and make data available to society in order to achieve sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%
“…This section explores the literature regarding three research questions and various heterogeneous users as background information for the study. On the user side, Shehata and Elgllab (2021)…”
Section: Heterogenous Open Data Usersmentioning
confidence: 99%